ANALISIS PENGARUH PERAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN MODERASI LOCUS OF CONTROL DAN BUDAYA ORGANISASI (Studi pada Satuan Kerja Perangkat Daerah Pemerintah Kota Semarang) - Rahardja, Rahardja; Andriyanto, Irsad (Universitas Islam Negeri Sunan Kudus, 2014)
This study was aimed to analyze the role of locus of control and organizational culture on the relationship between budgetary participation and managerial performance. Participation budget has been empirically tested positive influence on managerial performance. The study provides further explanation of the relationship by testing the moderating effects of locus of control and organizational culture, especially at the level of Satuan Kerja Perangkat Daerah (SKPD) Municipality of Semarang. The results showed that locus of control and organizational culture moderate the effect of budget participation on the performance majarial. The results of this study are expected to provide solutions in increasing performance on education so as to create good governance. The results of this study will contribute to the research-previous research, strengthen existing research concerning the relationship influence of budget participation and managerial performance, and to clarify the contingency factors that locus of control and organizational culture.